2023
DOI: 10.1108/jgr-09-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

Ecological footprint in a global perspective: the role of domestic investment, FDI, democracy and institutional quality

Abstract: Purpose The continuous increase in the negative gap between biocapacity and ecological footprint has remained globally persistent since early 1970. The purpose of this study is to examine the effect of foreign capital, domestic capital formation, institutional quality and democracy on ecological footprint within a global panel of 101 countries from 1995 to 2017. Design/methodology/approach The empirical procedure is based on data mix. To this end, this study uses a battery of testing and estimation approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Theoretically and empirically, there is mixed evidence on the relationship between FDI and environmental degradation. Studies by Pao and Tsai (2011), Munir and Ameer (2020), Shahbaz et al (2020), Yasmeen et al (2022), Emmanuel et al (2023), Naqvi et al (2023), Raza et al (2023) and Tabash et al (2023) found the worsening effect of FDI on environmental quality, which supports the pollution haven hypothesis. However, Zafar et al (2019), Rajpurohit and Sharma (2020), Arif et al (2022), Dada et al (2022), Saqib et al (2023), Sun et al (2022) and Ullah et al (2023) have shown that FDI has a favourable effect on environmental quality by supporting the pollution halo hypothesis.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Theoretically and empirically, there is mixed evidence on the relationship between FDI and environmental degradation. Studies by Pao and Tsai (2011), Munir and Ameer (2020), Shahbaz et al (2020), Yasmeen et al (2022), Emmanuel et al (2023), Naqvi et al (2023), Raza et al (2023) and Tabash et al (2023) found the worsening effect of FDI on environmental quality, which supports the pollution haven hypothesis. However, Zafar et al (2019), Rajpurohit and Sharma (2020), Arif et al (2022), Dada et al (2022), Saqib et al (2023), Sun et al (2022) and Ullah et al (2023) have shown that FDI has a favourable effect on environmental quality by supporting the pollution halo hypothesis.…”
Section: Introductionsupporting
confidence: 59%
“…(2022) in BRICS, Balsalobre-Lorente et al. (2023) in Asia–Pacific Economic Cooperation (APEC) countries, Emmanuel et al . (2023) in a global panel of 101 countries, Naqvi et al.…”
Section: Recent Literature Reviewmentioning
confidence: 99%
“…The study period is chosen due to data availability and it equally falls within the period of time that Cameroon started exploiting crude oil. We capture economic growth by GDP per capita growth in annual percentage (gdpc), such a measure has been used within literature ([ [67] , [68] , [69] , [70] ]). Renewable natural resource rents are proxied by Forest rents as a percentage of GDP (rnr) and non-renewable natural resource is proxied by Oil rents as a percentage of GDP (nrnr) in line with [ 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…In terms of environmental quality, the empirical investigation found that higher institutional qualities were better. Emmanuel et al [55] examined the impact of institutional quality on EF in a global panel of 101 countries from 1995 to 2017. The expected results show that raising the institutional quality of different estimators raises the atmosphere's level.…”
Section: Literature Reviewmentioning
confidence: 99%